An Evolutionary Arms Race Between Burkholderia pseudomallei and Host Immune System: What Do We Know? - Chomkatekaew, Chalita; Boonklang, Phumrapee; Sangphukieo, Apiwat; Chewapreecha, Claire (Frontiers in Microbiology, 2021)
better understanding of co-evolution between pathogens and hosts holds promise for better prevention and control strategies. This review will explore the interactions between Burkholderia pseudomallei, an environmental and opportunistic pathogen, and the human host immune system. B. pseudomallei causes “Melioidosis”, a rapidly fatal tropical infectious disease predicted to affect 165,000 cases annually worldwide, of which 89,000 are fatal. Genetic heterogeneities were reported in both B. pseudomallei and human host population, some of which may, at least in part, contribute to inter-individual differences in disease susceptibility. Here, we review (i) a multi-host - pathogen characteristic of the interaction; (ii) selection pressures acting on B. pseudomallei and human genomes with the former being driven by bacterial adaptation across ranges of ecological niches while the latter are driven by human encounter of broad ranges of pathogens; (iii) the mechanisms that generate genetic diversity in bacterial and host population particularly in sequence encoding proteins functioning in host - pathogen interaction; (iv) reported genetic and structural variations of proteins or molecules observed in B. pseudomallei – human host interactions and their implications in infection outcomes. Together, these predict bacterial and host evolutionary trajectory which continues to generate genetic diversity in bacterium and operates host immune selection at the molecular level.